2002
DOI: 10.1002/1521-3773(20020703)41:13<2281::aid-anie2281>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular-Wire Confinement of I2 Molecules in Channels of the Organic Zeolite Tris(o-phenylenedioxy)cyclotriphosphazene

Abstract: Efficient guest exchange: The organic zeolite analogue TPP⋅x(THF) (x=0.35–0.65) takes up I2 quickly when exposed to iodine vapor. The previously colorless crystals (a) color at the ends (b), and after 1–2 days the iodine has permeated all the way through the crystal (c). The conductivity values of the TPP⋅y(I2) crystals are of the same order as those of elemental I2. TPP=tris(o‐phenylenedioxy)cyclotriphosphazene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
107
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 26 publications
(17 reference statements)
3
107
1
Order By: Relevance
“…3. The E-D strength of the phenyl ring within TPP affects the stability of the adsorbent···adsorbate complex [7]. Therefore, we demonstrated herein a tight relation between the IP of TPP-like molecules and that of the free side fragment.…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…3. The E-D strength of the phenyl ring within TPP affects the stability of the adsorbent···adsorbate complex [7]. Therefore, we demonstrated herein a tight relation between the IP of TPP-like molecules and that of the free side fragment.…”
Section: Resultsmentioning
confidence: 56%
“…Studies focused on the stability of the hexagonal modification compared to compact guest-free monoclinic [5], the investigation of gas storage or aromatic guest insertion by advanced NMR techniques [6], the confinement of I 2 molecules by several crystallization procedures [7], and the insertion of dipolar molecules [8]. From TPP to some of its derivatives, it has been shown that the available space for absorbates can be modulated by the choice of the side group, which substitutes the dioxyphenylene in the former, the key-factor of the tunnel formation being reported to be the rigid "paddle wheel" molecular shape and the requirements of the crystal state [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously demonstrated, in-diffusion of I 2 into TPP(THF) 0.35 leads to a reduction of the content of THF. [14] Consequently, no empty channels would be needed for an uptake, i.e., filtering, of I 2 . The effectiveness of TPP acting in a filter setup was tested by passing a flow of 25 mL min -1 argon saturated with I 2 (25°C) through a column (diameter 3 mm, length 50 mm) filled with TPP(THF) 0.35 crystallites of an average size of 200 lm (Fig.…”
Section: Retention Of Radioactive Iodine Compoundsmentioning
confidence: 99%